Specialization in banking - Kristian Blickle; Cecilia Parlatore; Anthony Saunders (Federal Reserve Bank of New York, 2021)
Using highly detailed data on the loan portfolios of large U.S. banks, we document that these banks "specialize" by concentrating their lending disproportionately into one industry. This specialization improves a bank's industry-specific knowledge and allows it to offer generous loan terms to borrowers, especially to firms with access to alternate sources of funding and during periods of greater nonbank lending. Superior industry-specific knowledge is further reflected in better loan and, ultimately, bank performance. Banks concentrate more on their primary industry in times of instability and relatively lower Tier 1 capital. Finally, specialization counteracts a well-documented trend in reduced lending by large banks to opaque small and medium-sized enterprises.
Keywords: D4; G20; G21; 330; bank specialization; bank concentration; asymmetric information; loan performance; bank performance